A Novel Compressed Encrypted and Encoded Watermark Embedding Scheme for Digital Images - S, Rohith; K Sujatha, B (International Journal of Engineering and Technology, 2018)
In this research work a novel idea of compressed, encrypted and encoded watermark embedding scheme for digital images is proposed. Initially watermark is compressed using Huffman encoder. Compressed watermark is encrypted using combined binary key sequence Ki derived from sequence of logistic map and Lozi map. The compressed and encrypted binary watermark is encoded using (n,1) repetition code. This compressed, encrypted and encoded binary watermark is embedded in alternate locations of cover image pixels using of Least Significant Bit (LSB) and Second Least Significant Bit (SLSB). To study the watermarked image quality, parameters such as Signal to Noise Ratio (SNR) and Mean Square Error (MSE) are used. Also performance of the proposed system is compared with uncompressed, encrypted, encoded watermark embedding scheme. There is a significant improvement in MSE, SNR of watermarked image, when compressed watermark embedding scheme is compared to uncompressed watermark embedding scheme.
Keywords: Spatial domain watermarking; Lozi mapping; Logistic mapping; Huffman code; repetition code.